Objetividade e imparcialidade : uma análise filosófica - Coutes, Lígia Maria (2017)
The notion of scientific objectivity, conceived as one of the central virtues of scientific knowledge, consists in a fundamental concept in the modern scientific paradigm. However, there is a scarce literature dedicated to explore the definition of this notion, which has often made it be taken for granted. Scientific objectivity is discussed in different ways across different domains, such that one can find different definitions and discussions relating to this concept, which have sparkled different criticisms. Faced with this, the aim of this dissertation is to provide an analysis of the notion of scientific objectivity, and particularly of the notion of impartiality, aiming to reconstruct the historical development of this concept to understand how it became such an important notion in science. We start by tracing back the notion of scientific objectivity to the distinction between facts and values established in the seventeenth century. We discuss how this distinction was illustrated in Francis Bacon s theory of Idols. We show that Bacon was one of the first philosophers to sketch the ideas associated with the notion of objectivity . We then proceed to characterize the traditional notion of objectivity and its related theses: impartiality, neutrality, and autonomy, giving emphasis to the impartiality thesis. Moreover, we try to show that there are two radical interpretations of objectivity stemming from two distinct perspectives. On the one hand, scientific objectivity is seen as one central epistemological notion that supports the modern paradigm of science. On the other hand, objectivity is seen as an ideal notion of scientific practice that cannot be satisfied, thus giving us motivation to abandon it. The question that arises is whether these two radical views are the only plausible ones to understand the notion of scientific objectivity. In this dissertation, we hold that an alternative view is possible, and this view, which can be characterized as moderate, is illustrated by Susan Haack s Critical Common-Sensism. We thus conclude by providing an alternative definition of objectivity which can be fruitful in philosophy.